Initiative to improve the cardiogenic safety of antipsychotic medication in community mental health patients - Parks, Katherine Margaret (BMJ Open Qual, 2017)
Serious mental illness is reported to reduce a patient’s life expectancy by 15–20 years. This disparity is thought to be related to lifestyle factors, access to healthcare, poor health monitoring and the common use of antipsychotics, which can cause serious metabolic and cardiogenic side effects. Therefore, to reduce the risk of cardiac complications, both national and local guidance recommends annual ECG monitoring for patients on antipsychotics. Unfortunately this monitoring is not completed consistently at Manchester Mental Health and Social Care Trust, especially within community mental health teams. A small team of healthcare professionals conducted a quality improvement (QI) project from June 2015 to May 2016 with the aim of addressing this deficiency in care. A multidisciplinary approach was used to implement improvement in four key areas. Awareness of the need for monitoring, patient engagement with this process, identification of patients requiring monitoring and access to ECG equipment were all addressed as separate primary drivers for change over an 8-month period using a ‘Plan Do Study Act’ model of QI. Outcome, process and balancing measures were gathered monthly to track progress and improvement following the application of change. Compliance with annual ECG monitoring nearly doubled throughout the course of the project from 43% in June 2015 to a peak of 83% in February 2016. Improvement appeared to be sustained as the percentage of patients receiving the required monitoring remained significantly higher than baseline even after no further change interventions were being implemented (76%, 71%, 77%, March, April, May 2016). This QI project has shown that improvements can be made and has documented a recipe for how this change was achieved.